Enzymatically Cross-Linked Gelatin/Chitosan Hydrogels: Tuning Gel Properties and Cellular Response - da Silva, Marcelo A. (Macromol Biosci, 2014)
This work investigates the effect of combining physical and chemical gelation processes in a biopolymer blend: chitosan and tilapia fish gelatin. Chemical (C) gels are obtained by cross-linking with the microbial enzyme transglutaminase at 37 °C. Hybrid physical-co-chemical (PC) gels are cross-linked at 21 °C, below gelatin gelation temperature. These protocols provide two microenvironments for the gelation process: in C gels, both gelatin and chitosan are present as single strands; in PC gels, cross-linking proceeds within a transient physical gel of gelatin, filled by chitosan strands. The chitosan/gelatin chemical networks generated in PC gels show a consistently higher shear modulus than pure C gels; they are also less turbid than their C gels counterparts, suggesting a more homogeneous network. Finally, chitosan enhances the gels' shear modulus in all gels. Proliferation assays show that MC3T3 cells proliferate in these mixed, hybrid gels and better so on PC gels than in C mixed gels.